Contrast Enhancement Patterns of Acute Spinal Epidural Hematomas: A Report of Two Cases - Chang, Feng-Chi; Lirng, Jiing-Feng; Chen, Shing-Su; Luo, Chao-Bao; Guo, Wan-You; Teng, Michael Mu Huo; Chang, Cheng-Yen (American Journal of Neuroradiology, 2003)
Summary: The MR finding of an acute spinal epidural hematoma (SEH) can mimic epidural neoplastic or inflammatory lesions, because acute SEH appears hypointense on T1-weighted images and hyperintense on T2-weighted images. We report on two cases of acute SEH with unusual contrast enhancement patterns on MR images. Contrast enhancement can be an MR finding of acute SEH, especially in bleeding diathesis, which indicates an active lesion that needs early diagnosis and management.